BLOOD CELLS PROFILE IN UMBILICAL CORD OF LATE PRETERM AND TERM NEWBORNS - Anna Carolina Boni Rolim; Marley Aparecida Lambert; Juliana Policastro Grassano Borges; Samira Ali Abbas; José Orlando Bordin; Dante Mário Langhi Junior; Akemi Kuroda Chiba; Amélia Miyashiro Nunes dos Santos
ABSTRACT Objective: To describe the hematological profile in cord blood of late preterm and term newborns and compare blood indices according to sex, weight for gestational age and type of delivery. Methods: Cross-sectional study with late preterm and term newborns in a second-level maternity. Multiple gestation, chorioamnionitis, maternal or fetal hemorrhage, suspected congenital infection, 5-minute Apgar <6, congenital malformations, and Rh hemolytic disease were excluded. Percentiles 3, 5,10, 25, 50, 75, 90, 95 and 97 of blood indices were calculated for both groups. Results: 2,662 newborns were included in the sample, 51.1% males, 7.3% late preterms, 7.8% small for gestational age (SGA) and 81.2% adequate for gestational age (AGA). Mean gestational age was 35.6±1.9 and 39.3±1.0 weeks, respectively, for premature and term neonates. The erythrocytes indices and white blood cells increased from 34-36.9 to 37-41.9 weeks. Basophils and platelets remained constant during gestation. Premature neonates presented lower values of all blood cells, except for lymphocytes and eosinophils. SGA neonates presented higher values of hemoglobin, hematocrit and lower values of leukocytes, neutrophils, bands, segmented, eosinophils, monocytes and platelets. Male neonates presented similar values of erythrocytes and hemoglobin and lower leukocytes, neutrophils, segmented and platelets. Neonates delivered by C-section had lower values of red blood cells and platelets. Chronic or gestational hypertension induced lower number of platelets. Conclusions: Blood cells increased during gestation, except for platelets and basophils. SGA neonates had higher hemoglobin and hematocrit values and lower leukocytes. Number of platelets was smaller in male SGAs, born by C-section and whose mothers had hypertension.